FINANCIAL MECHANISM FOR IMPLEMENTING STATE POLICY IN THE FIELD OF RAILWAY FREIGHT TRANSPORTATION - Olga, Olga; Hoi, Nataliia; Nagornyak, Mykhailo (Public Management and Policy, 2025)
In the current conditions of Ukraine's integration into the European transport space and deepening economic transformations, the problem of improving the financial mechanism in the field of rail freight transportation is of particular relevance. Financial support for the functioning and development of this segment of the transport industry determines the level of implementation of state policy, the efficiency of logistics processes and the competitiveness of the national economy. The purpose of the article is to provide a theoretical and practical justification for ways to improve the financial mechanism in order to increase the efficiency of the implementation of state policy in the field of rail freight transportation. As a result of the research, the essence and structure of the financial mechanism were revealed, its instruments and functions in the transport policy of the state were characterized. The current state of financial support for rail freight transportation in Ukraine was analyzed, taking into account data for 2020–2024. The main problems of the current financing model were identified, in particular: the dominance of the subsidy approach, the absence of a stable source of capital investment, insufficient participation of private capital and weak integration with European financial instruments. A set of measures to improve the financial mechanism is proposed, including diversification of funding sources, activation of public-private partnerships, stimulation of investments and introduction of digital technologies in financial management. It is concluded that modernization of the financial mechanism is a key condition for increasing the efficiency of railway transport, ensuring its sustainable development and compliance with European standards.